The Effect of the Use of Project Based Learning (PjBL) Learning Model on the Creativity and Metacognition of Class X Students on Ecoprinting Materials of the Green Chemistry Concept - Noor Hiqmah; Sri Handayani (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aimed to analyze the effect of implementing the Project-Based Learning (PjBL) model through ecoprinting activities on the metacognitive skills and creativity of tenth-grade students in learning green chemistry. A quasi-experimental method with a nonequivalent pretest-posttest control group design was employed. The sample consisted of 72 tenth-grade students from SMA Negeri 4 Tarakan, divided into an experimental group (Class X-2, n = 36), which received PjBL through ecoprinting activities, and a control group (Class X-8, n = 36), which received Inquiry-based learning. Data were collected using pretest and posttest instruments to measure metacognitive skills and observation sheets to assess students’ creativity during the learning process. Descriptive analysis indicated that the experimental group achieved higher mean scores in both metacognitive skills and creativity than the control group. The Independent Samples t-test revealed that PjBL through ecoprinting activities significantly improved students’ metacognitive skills (p < 0.001) and creativity (p < 0.001). In addition, MANOVA results showed a significant simultaneous difference between the two groups across both dependent variables (Hotelling’s Trace, p < 0.001). These findings demonstrate that PjBL integrated with ecoprinting is an effective, contextual, and student-centered instructional approach for enhancing metacognitive skills and creativity in green chemistry learning.